A research on exit strategy of foreign venture capital investment in Chinese private business sector - Jin, Xin (2007)
With the emergence of knowledge economy and the development of science and technology, more and more entrepreneurs who seeking venture capital funds to finance their great inventions become much more appreciated. As a result, the essential of venture capital investment has encouraged more people to fulfill their entrepreneurial ambition. As the major scientific and technological development driving force, the entrepreneurial ventures derived from latest innovations attempt to take part in reinforcing the social and economic developments are recognized.